Conditioned medium from neural stem cells inhibits glioma cell growth - Li, Z.; Zhong, Q.; Liu, H.; Liu, P.; Wu, J.; Ma, D.; Chen, X.; Yang, X. (Cellular and Molecular Biology, 2016)
Malignant glioma is one of the most common brain tumors in the central nervous system. Although the significant progress has been made in recent years, the mortality is still high and 5-year survival rate is still very low. One of the leading causes to the high mortality for glioma patients is metastasis and invasion. An efficient method to control the tumor metastasis is a promising way to treat the glioma. Previous reports indicated that neural stem cells (NSCs) were served as a delivery vector to the anti-glioma therapy. Here, we used the conditioned medium from rat NSCs (NSC-CM) to culture the human glioblastoma cell lines. We found that NSC-CM could inhibit the glioma cell growth, invasion and migration in vitro and attenuate the tumor growth in vivo. Furthermore, this anti-glioma effect was mediated by the inactivation of mitogen activated protein kinase (MAPK) pathway. Above all, this study provided the direct evidence to put forward a simple and efficient method in the inhibition of glioma cells/tumor growth, potentially advancing the anti-glioma therapy.